Infecção relacionada com a prestação de cuidados de saúde - Pina, Elaine (2018)
Healthcare related infections constitute a major public health problem although, in Portugal, they have not been given high priority. This study was undertaken to describe and quantify hospital acquired infections and more specifically nosocomial bloodstream infections and the correspondent morbidity and mortality from the information obtained in prevalence and incidence studies conducted by the Infection Control Project/National Infection Control Programme. From the undertaken analysis performed we have observed an increase in bloodstream infections probably associated to the enhanced use of invasive devices. The design of the analyzed studies does not permit the identification of specific risk factors nor the analysis of related structures and practices adopted for the prevention of infections. Although comparison with data from other European countries did not show significant differences, recent studies have shown that it is possible to achieve rates of 0% in catheter associated bloodstream infections. We therefore conclude that it is justified to undertake further research to address this problem in more detail so as to take steps for evidence-based interventions to obtain the 0% rates achieved by some institutions.